2016
DOI: 10.1371/journal.pone.0151890
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Prevents Cisplatin-Induced Cognitive Impairment and Brain Damage in Mice

Abstract: RationaleChemotherapy-induced cognitive impairment, also known as ‘chemobrain’, is now widely recognized as a frequent adverse side effect of cancer treatment that often persists into survivorship. There are no drugs available to prevent or treat chemotherapy-induced cognitive deficits. The aim of this study was to establish a mouse model of cisplatin-induced cognitive deficits and to determine the potential preventive effects of the anti-diabetic drug metformin.ResultsTreatment of C57/BL6J mice with cisplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 59 publications
(65 reference statements)
6
95
0
3
Order By: Relevance
“…Recent studies have documented that chemotherapy can disrupt hippocampal neurogenesis (Dietrich et al 2006), and is associated with alterations in white matter integrity (Inagaki et al 2007; Deprez et al 2013). Recent rodent studies have shown that cisplatin inhibits neurogenesis and disrupts cognitive function (Manohar et al 2014; Vichaya et al 2015), and that metformin may prevent cisplatin-related central neurotoxicity (Zhou et al 2016). Additional studies addressing the neurotoxicity of specific chemotherapeutic agents would contribute to our understanding of the underlying mechanisms, and the development of preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have documented that chemotherapy can disrupt hippocampal neurogenesis (Dietrich et al 2006), and is associated with alterations in white matter integrity (Inagaki et al 2007; Deprez et al 2013). Recent rodent studies have shown that cisplatin inhibits neurogenesis and disrupts cognitive function (Manohar et al 2014; Vichaya et al 2015), and that metformin may prevent cisplatin-related central neurotoxicity (Zhou et al 2016). Additional studies addressing the neurotoxicity of specific chemotherapeutic agents would contribute to our understanding of the underlying mechanisms, and the development of preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…All behavioral assays were performed in a blinded setup. NOPR was performed as we have previously described [2]. In brief, mice were transferred to a testing arena (46.99 cm × 25.4 cm) containing two identical objects placed against one side of the arena for 5 min (training phase) and then returned to their home cages for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The integrity of the neurogenic stem cell niche is crucial for adequate cognitive function [27], [28]; we have found that cisplatin reduces white-matter integrity as analyzed at the level of the coherency of myelin basic protein (MBP) fibers in the cingulate cortex [2]. We therefore performed fixation and immunostaining of neuronal precursors in the subventricular zone (SVZ) and dentate gyrus (DG), as previously described [3].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations